Pilot study on the upgrading configuration of UASB-MBBR with two carriers: Treatment effect, sludge reduction and functional microbial identification. (December 2020) - Liu, Yonghong; Wang, Ning; Wei, Yuxi; Dang, Kang; Li, Miaojie; Li, Yaozhong; Li, Qinghui; Mu, Ruihua
Graphical abstract: Highlights: The low-cost process of anaerobic-aerobic system was operated on a pilot scale. The anaerobic carriers had similar performance to polyvinyl alcohol but lower cost. The anaerobic and anoxic zones coexisted in aerobic polyurethane carriers. Bacteria, archaea and fungi contribute to sludge reduction and nutrient removal. Filamentous bacteria may be involved in initial attachment and renewal of biofilm. Abstract: Two kinds of biocarriers were adopted and a combined process of "AMC (Anaerobic microorganism carrier)-UASB and PBG (Porous bio-gel)-MBBR" was operated at the pilot scale for the treatment of real textile wastewater. The influence mechanism of the two carriers on the start-up, pollutant removal and sludge reduction were investigated within 118 days of operation. The dominant functional bacteria in anaerobic and aerobic systems were identified by high-throughput sequencing, and the possible ways and related mechanisms of nutrient removal and sludge reduction were analyzed based on the data. 37.0 ± 7.5 % and 53 ± 12.7 % of COD removal efficiencies were achieved in anaerobic system and aerobic system, respectively. Ammonia nitrogen concentration decreased from 20 to 45 to 3.49 ± 0.54 mg/L after treatment. An anaerobe was found to be closely related to color removal, which existed in both anaerobic and aerobic systems, achieving 84.0 % of color removal. With the operation of the system, the sludge yield decreased gradually. The sludge yields of anaerobic and aerobic systems were calculated individually and compared with similar studies. Aging biofilms were characterized to explore the factors associated with biofilm renewal.